The Radical Desire for Life. From Immanence in Michel Henry to Alterity in Saint Augutine - Rosales Meana, Diego I. (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
The principal purpose of this text is to show that Michel Henry’s radicalization of phenomenology conduces to a problematic interpretation of the world and human desire, and to proposea solution to the problem from the philosophy of Augustine of Hippo. If for Henry, Life is absolute immanence, for Augustine it is also extasis. If for the first desire has to be reduced to mere immanence,for the later this desire (appetitus) is one of the ways in which man can encounter the Absolute.